“COMBINACIÓN DE Beauveria bassiana CON POLVOS INERTES PARA EL CONTROL DE Cosmopolites sordidus” - Zurita Chavarria, Victor Emilio (2024)
Cosmopolites sordidus is a significant pest affecting banana production, known for its resistance to chemical insecticides, highlighting the need for alternative control methods. This research aimed to identify the effect of the combination of the entomopathogenic fungus Beauveria bassiana with inert powders (kaolin, diatomaceous earth, and lime) and insecticide (Imidacloprid) for the control of C. sordidus.